Pathogenic cis p-tau levels in CSF reflects severity of traumatic brain injury. (3rd June 2022) - Mohsenian Sisakht, Alireza; Karamzade-Ziarati, Najme; Jahanbakhshi, Amin; Shahpasand, Koorosh; Aghababaei, Samareh; Ahmadvand, Omid; Azar, Maziar; Fattahi, Arash; Zamanzadeh, Selva
ABSTRACT: Traumatic brain injury (TBI) is the main cause of death and disability among young people. Following TBI, immune system activation and cytokine release induce kinase activity and hyperphosphorylation of tau protein, a structural molecule in axonal microtubules. The cis configuration of phosphorylated tau at Th231 is extremely neurotoxic and is having a prion nature, spreads to brain areas as well as CSF. We examined the cerebrospinal fluid (CSF) cis p-tau levels in 32 TBI patients and 5 non-TBI controls to find out the correlation with TBI severity.    CSF samples were drained 5–7 days after TBI and subjected for ELISA analysis with anti cis p-tau and β-amyloid antibodies. We had no patients with mild TBI, two patients with moderate (6.2%), 23 patients with severe (71.9%), and 7 patients with critical TBI (21.9%). While mean CSF β-amyloid in TBI and control groups did not show a statistically significant difference, the mean CSF cis p-tau level was significantly higher in the TBI group than the control samples. Also, intergroup analysis demonstrated that CSF cis p-tau levels were statistically different according to the head injury severity. Although CSF cis p-tau increased in the TBI patients, β-amyloid did not show a significant difference between patients and controls. Also, we observed an obvious negative correlation between CSF cis p-tau levels and GCS scores. Therefore, future researches on suppression of cis P-tau production or removing previously produced cis P-tau could be a suitable approach in treating TBI in order to prevent tauopathies and future neurodegeneration.